Decoding sebaceous gland functions and diseases: insights from domestic animals - Helga Pfannkuche; Juliane Maus; Kathrin M. Engel; Jürgen Schiller; Marlon R. Schneider (Veterinary Research Communications, 2026)
Skin sebaceous glands (SGs) synthesize and secrete sebum, a mixture of lipids and cellular debris that defends the external body surface against physicochemical challenges. Recent data define the SG as a dynamic entity with potential functions beyond skin protection, including immunomodulatory actions and the regulation of energy metabolism. We postulate that the SG also has important, unrecognized roles in physiological and pathological processes in domestic animals. Conversely, data derived from domestic animals may have translational relevance for humans. This review article summarizes SG structural and functional features in the most widespread species domesticated for food (cattle, sheep, goats, and pigs), work (horses), and companionship (dogs and cats). Our survey reveals hitherto unrecognized roles of the SG in diverse pathophysiological processes. Among other fascinating facts, we learn that sebum has an exquisite and unique lipid composition in each of the considered species. Furthermore, sebum is essential for e.g., wool production but also a carrier for the most important cat protein causing allergic reactions in humans, and dogs and cats may develop a SG-related skin illness resembling acne that is potentially relevant as a model for the human disease. This critical review provides a foundation for future interdisciplinary studies in a largely neglected area with great potential for advancing animal welfare and human health.